Development of Android-based Bimanji e-media for Innovation Learning Resources on Ecosystem Material - Hurrun In Nikmah; Yuni Pantiwati; Nurwidodo Nurwidodo; Elly Purwanti (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: The rapid development of technology in the Industrial Revolution 4.0 era significantly affects various sectors, especially education. This research aimed to develop an innovative Android-based educational game, Bimanji (Biology Jumanji), as an interactive learning medium for ecosystem material in junior high school. Methodology: The study employed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The product was tested at Junior High School of  Muhammadiyah 1 Surabaya. Data was collected through observations, interviews, documentation, and validation questionnaires by media, material, language, IT experts, and student and teacher responses. Bimanji integrates the concept of the popular Jumanji board game with interactive, contextual learning content, including 2D animation and multiplayer features. Findings: The content covers biotic-abiotic interactions, trophic levels, food chains, food webs, and ecological awareness. Validation results showed that Bimanji achieved a 92 % average validity score, indicating a high feasibility level without requiring significant revisions. Practicality tests with 16 students and teacher also resulted in high scores (93 % and 88 %, respectively), confirming its usability and effectiveness. The game enhances students' understanding of ecosystem concepts and motivation through fun and collaborative digital learning. Contribution: This research concludes that Bimanji is a highly valid, practical, and accessible educational medium suitable for classroom and independent learning. Limitations involve limited field trials and require broader implementation. Future development may integrate augmented reality to enrich the user experience further.